2017
DOI: 10.1097/mej.0000000000000305
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a media campaign on resuscitation performance of bystanders: a manikin study

Abstract: A simple and cost-efficient media campaign appears to enhance the performance of chest compressions. Ventilation performance and the rate of CPR performance were not increased by the campaign.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…This dataset (available in the accompanying Supplementary Excel Spreadsheet file) summarises, in 28 tables, the psychomotor skill data extracted from 31 primary peer-reviewed articles that met the inclusion criteria for the related systematic review [2], [3], [4], [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32]. The psychomotor skills for which data were extracted and reported were: compression rate, compression depth, duration of interruptions to compressions, chest recoil, hand placement, proportion of adequate or ’correct’ compressions, ventilation volume, compression-to-ventilation ratio, duty cycle and overall skills.…”
Section: Datamentioning
confidence: 99%
“…This dataset (available in the accompanying Supplementary Excel Spreadsheet file) summarises, in 28 tables, the psychomotor skill data extracted from 31 primary peer-reviewed articles that met the inclusion criteria for the related systematic review [2], [3], [4], [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32]. The psychomotor skills for which data were extracted and reported were: compression rate, compression depth, duration of interruptions to compressions, chest recoil, hand placement, proportion of adequate or ’correct’ compressions, ventilation volume, compression-to-ventilation ratio, duty cycle and overall skills.…”
Section: Datamentioning
confidence: 99%
“…In the steps of the survival chain, activation of emergency response, highquality cardiopulmonary resuscitation (CPR), and defibrillation are the three most important and fundamental skills that can be performed by bystanders or first responders to a cardiac arrest [1]. Global resuscitation data indicated that survival rates range from 4.6% to 32%, and bystander CPR rates range from 20% to 51% [2][3][4][5][6][7][8][9]. Compared to this global data, Taiwan's bystander CPR rate is relatively low and should be addressed by first aid educators [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, more objective methods of assessing these skills, such as CPR manikins with specific software, [8,9] mechanical devices, [1012] etc, provide excellent accuracy and feedback and are becoming more widely used. Moreover, retrospective analysis of video recordings is increasingly being used in pediatric CPR training, and preliminary data supports the feasibility of this technique in assessing the quality of CPR in adults.…”
Section: Introductionmentioning
confidence: 99%